Pojmovanja ustvarjalnosti in stališča do te pri sedanjih in bodočih vzgojiteljicah predšolskih otrok - Dolenc, Petra (Revija za elementarno izobraževanje, 2020)
Educators' perceptions and attitudes towards creativity significantly determine their teaching practice. Therefore, the study aimed to examine the prevailing conceptions of creativity among pre-service and in-service preschool teachers. A multi-part questionnaire was designed and completed by two groups: preschool teachers and early childhood education students. Generally, participants demonstrated adequate theoretical knowledge in the field of creativity; however, there were minor discrepancies between the groups, which may be the result of some implicit beliefs about creativity and the perception of their role in supporting creativity of preschool children.
Keywords: creativity; implicit theories of creativity; implicitne teorije o ustvarjalnosti; predšolska vzgoja; preschool education; ustvarjalnost